Effect heterogeneity in responding to performance-based incentives: a quasi-experimental comparison of impact on health service indicators between hospitals and health centers in Malawi - Brenner, Stephan; Chase, Rachel P.; McMahon-Rössle, Shannon A.; Lohmann, Julia; Makwero, Christopher J.; Muula, Adamson S.; De Allegri, Manuela (Health systems & reform, 2020)
Heterogeneity of effects produced by performance-based incentives (PBIs) at different levels of care provision is not well understood. This study analyzes effect heterogeneities between different facility types resulting from a PBI program in Malawi. Identical PBIs were applied to both district hospitals and health centers to improve the performance of essential health services provision. We conducted two complementary quasi-experiments comparing all 17 interventions with 17 matched independent control facilities (each 12 health centers, five hospitals). A pre- and post-test design with difference-in-differences analysis was used to estimate effects on 14 binary quality indicators; interrupted time series analysis of monthly routine data was used to estimate effects on 11 continuous quantity indicators. Effects were estimated separately for health centers and hospitals. Most quality indicators performed high at baseline, producing ceiling effects on further measurable improvements. Significant positive effects were observed for stocks of iron supplements (hospitals) and partographs (health centers). Four quantity indicators showed similar positive trend improvements across facility types (first-trimester antenatal visits, voluntary HIV-testing of couples, iron supplementation in pregnancy, vitamin A supplementation of children); two showed no change for either type of facility (skilled birth attendance, fully immunized one-year-olds); five indicators revealed different effect patterns for health centers and hospitals. In both health centers and hospitals, the largely positive PBI effects on antenatal care included resilience against interrupted supply chains and improvements in attendance rates. Observed heterogeneity might have been influenced by the availability of specific resources or the redistribution of service use.
Gesehen am 30.07.2020